Large-sized polystyrene microplastics induce oxidative stress in AML12 cells - Bitian Zhao; Rui Liu; Shuhao Guo; Shiyu Li; Zekai Huang; Yihan Wang; Cuiping Yu; Zhijun Hou; Yuanyuan Zhang; Yanlong Zhang; Xuedong Liu (Scientific Reports)
Abstract Microplastics (MPs), particularly those exceeding 20 μm in diameter, are increasingly detected in environment and animal tissues, yet their cytotoxicity remains poorly understood. While existing studies focused on MPs with relatively small sizes (≤ 20 μm) or nanoplastics (NPs), the biological impacts of large-sized MPs and amino-modified MPs are underexplored. In this study, we investigated the oxidative stress (OS)-mediated responses of alpha mouse liver 12 (AML12) cells to 50 μm polystyrene MPs (PS-MPs) and polystyrene-amine modified MPs (PS-NH2-MPs) at concentrations of 0, 0.05, 0.1, 0.2, and 0.5 mg/mL for a duration of 48 h. Our investigation particularly emphasised on responses of apoptosis and ferroptosis. Intriguingly, exposure to PS-MPs at concentrations below 0.5 mg/mL did not induce significant ferroptosis-related alterations. However, at 0.5 mg/mL, PS-MPs triggered a significant increase in intracellular reactive oxygen species and reduced cell viability, paralleled by upregulated Caspase-9 mRNA expression, suggesting OS-driven apoptotic priming. Notably, surface functionalization with PS-NH2-MPs did not amplify these effects compared to pristine PS-MPs, indicating particle size dominate hepatocyte responses. These findings provide a toxicological paradigm for large-sized MPs, emphasising OS as a pivotal evaluation criterion for risk assessment. These results provide a novel perspective for environmental monitoring of MPs.